Spatial variation in the mutation rate within the plant shoot apical meristem - Kirk R. Amundson; Mohan P. A. Marimuthu; Oanh Nguyen; Konsam Sarika; Isabelle J. DeMarco; Angelina Phan; Isabelle M. Henry; Luca Comai (Proceedings of the National Academy of Sciences, 2025)
The potential impact of new mutations on organismal function and evolution depends on the developmental fate of the affected cells. Stem cells in the shoot apical meristem form much of the plant body, but only those in the L2 can form gametes. This raises the question of whether the mutation rate is optimized for this developmental plan. To test this, we compare stem cell mutations accumulated over decades of clonal propagation in two potato varieties with those arising during leaf-cell regeneration. By sequencing DNA from layer-enriched cell fractions, we found that variant allele frequencies in whole-leaf DNA can predict a mutation’s layer of origin. We further observed that mutations accumulate independently in L1 but jointly in L2 and L3. In cultivar Desiree, L1 mutation rates were fourfold higher than in deeper layers, suggesting germline-progenitor protection. In Red Polenta, layer-specific DNA from regenerants marked by a periclinal chromosomal translocation revealed a similar, though subtler, bias, with L1 exhibiting a 1.6-fold higher rate. In stark contrast, mutations during regeneration of differentiated cells were fiftyfold more frequent and bore a pronounced 8-oxoguanine signature confined to intergenic regions. Across all samples—and consistent with enhanced repair or purifying selection—the genic mutation rate was less than half that of intergenic regions. These findings indicate that plants employ mechanisms to restrict mutations according to cellular context and genomic region and suggest that the layered organization of angiosperm meristems evolved to balance genetic fidelity with adaptability